Usability criteria for the design and construction of videogames [Criterios de usabilidad para el diseño e implementación de videojuegos] (2020)
Usability has become a fundamental attribute for the development of interactive and competitive applications within the software industry, which allows software systems to fulfill the purpose for which they were built, as well as to consider the type of users to whom these systems are directed. For the design and evaluation of usability in the specific context of video games, Pinelle proposed ten general usability heuristics. In this paper we propose a set of criteria in terms of questions associated with each heuristic principle in order to evaluate its compliance in a timely manner, and an inspection tool to verify that these criteria are met. The built tool aims to support the conduct of inspections of usability in videogames at the academic level and within the software development companies. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.